Climate Finance and Green Banking Practices in Nepalese Commercial Banks - Bipana Shreshtha; Gyan Mani Adhikari (Journal of Business and Social Sciences, 2025)
The paper challenges the readiness of Nepalese business banks to embrace climate finance and green banking operations in the framework of the high susceptibility of the country to climatic conditions and its adherence to sustainable development. Although the emission of Nepal towards the global green house gas target is minimal, Nepal is facing serious climate-based risks such as the outburst of glacier lakes, unpredictable monsoon cycles, and loss of biodiversity. The banking sector being a key financial intermediary has a primary role of making sure that the capital flows into climate-resilient and sustainable projects that are also environmentally friendly. The study utilizes a mixed-method design by examining secondary data obtained in Nepal Rastra Bank, the annual reports of commercial banks, sustainability reports and available green banking frameworks. The result shows that, although the Nepali banks have already made some initial environmental moves like paperless banking and energy-saving, they still have critical flaws in climate risk analysis, green lending portfolio, and capacity building. The main barriers include regulatory confusion, a lack of technical skills and knowledge, lack of awareness among the stakeholders, and lack of financial incentives. This means that the readiness of Nepalese commercial banks to climate financing seems to be at an embryonic level and as such, requires well-structured policy frames, capacity development programmes, and global partnerships to attain the climate agenda in the nation and play a role in the global shift towards a low-carbon economy.